Safety and Effectiveness of Fluoroscopy-Guided Acupotomy for Carpal Tunnel Syndrome: Protocol for a Pilot Randomized, Patient-Assessor Blind, Parallel Clinical Trial - Muhack Yang; Jae Kyoun Kim; Gun Woo Park; Eunhye Cha; Jongwon Jang; Jihye Seo; Sangkwan Lee; Sungchul Kim (MEDrang Inc., 2019)
Background In Korean medicine, carpal tunnel syndrome is treated by stimulating the acupoints around the wrist. Although a deep understanding of anatomy and guidance is needed to stimulate these acupoints to avoid undesirable side-effects, currently there are no published guidelines for acupotomy treatment. The aim of this study is to evaluate the effectiveness and safety of fluoroscopy-guided acupotomy compared with conventional acupotomy treatment. Methods This is a randomized, patient-assessor, patient blind, parallel clinical trial. A total of 30 patients will be enrolled at Wonkwang University Gwangju Hospital, and will be allocated to either an experimental group or a control group. The experimental group will be treated using fluoroscopy-guided acupotomy and the control group will be treated using the conventional acupotomy method. Results The primary outcome measure will be identification of a cross-section area of the median nerve measured by ultrasonography, and the secondary outcome measure will be the alleviation of pain measured by the Visual Analogue Scale, improvement in the Nerve Conduction Study, Tinel test, Phalen's test, EuroQol 5-dimension scale, and Boston Carpal Tunnel Questionnaire score. Safety components will be measured by monitoring vital signs, electrocardiographs, blood tests, general chemical tests, urine tests and pregnancy tests. In addition, observations for adverse effects will be performed during the trial. Conclusions This study will provide a more effective, and less harmful way of treating carpal tunnel syndrome compared with conventional acupotomy. Fluoroscopy-guided acupotomy will help practitioners to be accurate in direction and depth of the needle for treating carpal tunnel syndrome.